Pengembangan Buku Saku Etnobotani Tanaman Aromatik Suku Melayu Sambas - Linda Lostari; Hanum Mukti Rahayu; Mahwar Qurbaniah (Postgraduate, University of Mataram, 2025)
This study aims to develop learning media in the form of an ethnobotanical pocket book of aromatic plants based on the local wisdom of the Sambas Malay community. The development was conducted using the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The results of the analysis showed a lack of learning media that is contextual and in accordance with the student's environment. The pocket book developed contains a description of the morphology, benefits, and utilisation of aromatic plants in the traditions of the Sambas Malay community. Expert validation showed that this pocket book was very feasible to use with a material expert validation score of 89%, linguist 88%, and media expert 99%. Implementation was carried out through small and large scale trials on grade X students at SMA Negeri 4 Sungai Raya. The trial results showed a very good response with a score of 95% on the small scale trial and 93% on the large scale. This pocket book is effective to be used as a contextual, informative, and supportive biology learning media for local culture preservation.